Manejo de nutrientes por sitio especifico en el cultivo de arroz en la zona de Babahoyo - Santillán Duchi, Carlos Humberto (2013)
In the grounds of the farm "San Pablo" belonging to the Faculty of Agricultural Sciences, Technical University of Babahoyo, a trial was conducted in rice varieties 'Iniap 15' and 'S - FL - 09', in the presence of levels chemical fertilizer, 0 – 60 – 90 – 44 – 36; 200 – 0 – 90 – 44 – 36; 200 – 60 – 0 – 44 – 36; 200 – 60 – 90 – 44 – 36; 200 – 60 – 90 – 0 – 36; 200 – 60 – 90 – 44 – 0 y 92 – 23 – 30 – 0 – 0 (program used by farmers) of N, P2O5, K2O, S and MgO, respectively, in order to: 1) evaluate the effect of nutrient management for specific site (SSNM) in rice, 2) determine the appropriate level of nutrition to maximize performance grain, 3) quantify the agronomic efficiency co9n management employment site-specific nutrient (SSNM), and 4) Economic analysis of grain yield based on the cost of production of the treatments.